A sustainable approach for the removal methods and analytical determination methods of antiviral drugs from water/wastewater: A review - Eryildiz, Bahriye; Yavuzturk Gul, Bahar; Koyuncu, Ismail (Elsevier BV, 2022)
In the last years, antiviral drugs especially used for the treatment of COVID-19 have been considered emerging contaminants because of their continuous occurrence and persistence in water/wastewater even at low concentrations. Furthermore, as compared to antiviral drugs, their metabolites and transformation products of these pharmaceuticals are more persistent in the environment. They have been found in environmental matrices all over the world, demonstrating that conventional treatment technologies are unsuccessful for removing them from water/wastewater. Several approaches for degrading/removing antiviral drugs have been studied to avoid this contamination. In this study, the present level of knowledge on the input sources, occurrence, determination methods and, especially, the degradation and removal methods of antiviral drugs are discussed in water/wastewater. Different removal methods, such as conventional treatment methods (i.e. activated sludge), advanced oxidation processes (AOPs), adsorption, membrane processes, and combined processes, were evaluated. In addition, the antiviral drugs and these metabolites, as well as the transformation products created as a result of treatment, were examined. Future perspectives for removing antiviral drugs, their metabolites, and transformation products were also considered.
Keywords: Article